2007
DOI: 10.1007/s11816-007-0031-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sex in Simmondsia chinensis (Jojoba) using RAPD markers

Abstract: Simmondsia chinensis (Link) Schneider, a multipurpose dioecious shrub of arid zones, has emerged as a cash crop. It is being cultivated for its seeds which store liquid wax whose properties are similar to spermaceti (Sperm whale oil), a substitute for petro products and precious high-priced lubricants. Jojoba is a slow-growing desert shrub having a male biased (5:1; male:female ratio) population. Since there is no method available to determine the sex at the seedling stage, current investigations have been car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 18 publications
0
52
1
Order By: Relevance
“…The seed is the main prapagule for jojoba and the plant takes 3-4 years to start flowering. Jojoba is a slow developing plant showing a male dominated (male:female::5:1) population (Agrawal et al 2007). Due to this male biased population and the ability of one male to pollinate many females in jojoba, the Indian farmers have to eliminate a huge number of male plants for maximizing the number as well as growth of commercially important female plants.…”
Section: Jojoba [Simmondsia Chinensis (Link) Schneider]mentioning
confidence: 99%
See 1 more Smart Citation
“…The seed is the main prapagule for jojoba and the plant takes 3-4 years to start flowering. Jojoba is a slow developing plant showing a male dominated (male:female::5:1) population (Agrawal et al 2007). Due to this male biased population and the ability of one male to pollinate many females in jojoba, the Indian farmers have to eliminate a huge number of male plants for maximizing the number as well as growth of commercially important female plants.…”
Section: Jojoba [Simmondsia Chinensis (Link) Schneider]mentioning
confidence: 99%
“…Although sexual differentiation of jojoba seedlings cannot be done cytologically since jojoba sex chromosomes are not distinguishable through cytological methods (Hosseini et al 2011), a number of molecular markers have been employed for determination of sex in jojoba. Molecular study by Agrawal et al (2007) identified a male-specific RAPD marker (OPG-05) producing 1400 bp amplicon in S. chinensis (Link) Schneider. Another study documented two male-specific and one female-specific RAPD markers along with PCR-based sex determination in jojoba by sexdetermining region Y (Sry) gene primers and random primers (Mohasseb et al 2009).…”
Section: Jojoba [Simmondsia Chinensis (Link) Schneider]mentioning
confidence: 99%
“…Sex determination in papaya by using PCR based RAPD molecular marker was reported by several authors from various countries like in Japan (Ursaki et al, 2002), Hawaii (Deputy et al, 2002), Brazil (Lemos et al, 2002) and India (Parasnis et al, 1999). In Salix viminalis (Alstrom-Rapaport et al, 1998), Encephalartos natalensis (Prakash & Staden, 2006), Borassus flabellifer , Simmondsia chinensis (Agrawal et al, 2007) and Pandanus fasciculalris (Vinod et al, 2007) also sex is determined by using PCR based RAPD molecular marker.…”
Section: Micropropagationmentioning
confidence: 99%
“…Differing from most of the cultivated crop species, jojoba has slow-growing habit, difficulties in the determination of sex at the early seedling stages, a male-biased (5:1; male: female) ratio and low seed yield (Benzioni and Vaknin 2002;Agrawal et al 2007;Sharma et al 2008). Commercial plantations of jojoba are mainly established using cuttings, or in a few cases grafting, resulting in a narrow genetic diversity that may cause the low seed yield (Dunstone et al 1985).…”
Section: Introductionmentioning
confidence: 99%